A method for preparing a water-based coating composite material

Through the use of UV cured water-based epoxy resin coating, the problem of maintaining the anodic film channel structure is solved, and the high corrosion resistance and wear resistance of the aluminum alloy surface is achieved, which meets a variety of customer needs and simplifies the production process.

CN116410660BActive Publication Date: 2025-01-14JIANGXI KUN-LONG NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310223875.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2025-01-14
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively maintain the anodized film channel structure, resulting in insufficient corrosion resistance and wear resistance. After the aluminum alloy surface treatment, customer needs are unknown, resulting in limited production process.

Method used

UV-cured aqueous epoxy resin coating is used as the transition layer, and the anodic channel structure is maintained through pretreatment, anodizing, pore reaming and vacuum freeze-drying, and negative pressure drying and UV photocuring technology ensures that the paint is fully entered. Fill in the hole.

Benefits of technology

Effectively maintain the anodized pore structure, easy to peel, suitable for a variety of customer needs, improves corrosion resistance and wear resistance of aluminum alloy surfaces, and reduces the complexity of the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116410660B_ABST
    Figure CN116410660B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a water-based coating composite material. The surface coating material of the prepared aluminum alloy composite material can effectively enter the anodic oxidation pores and can effectively maintain the pore structure after curing. The coating is easy to peel off and can be easily peeled off in a conventional paint stripper. After peeling, hydrothermal sealing, inorganic salt sealing, or coating polymer sealing can be selected, and the secondary utilization effect of the aluminum material is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a water-based coating composite material, relates to a UV curing water-based coating, and particularly relates to a water-based coating composition for maintaining the pore structure of an anodic oxide film. Background Art

[0002] Paints are generally cured by heat and light. Heat curing and light curing use heat and light to crosslink the paint, but many substrates are heat-sensitive materials that will deform or even damage the substrate at high temperatures. In addition, heat curing has the disadvantages of long time and inconvenient operation, which limits its application. UV curing technology has the advantages of fast curing speed, simple operation, low cost, and small amount of solvent, so light curing technology has important applications in the coating industry. The light curing mechanism is that the unsaturated double bond groups in the resin are attacked by free radicals produced by the initiator, thereby opening the double bonds. This process is called the chain initiation process; then the unsaturated double bonds continue to be attacked by free radicals and continue to grow. This process is called the chain growth process. The chain growth process is very rapid, and a highly cross-linked structure can be formed in just a few seconds.

[0003] Water-soluble UV-curable coatings are increasingly valued due to their advantages such as energy saving, environmental protection, low viscosity, and ease of spraying. They have become a hot topic for domestic and foreign scholars. Photoinitiators, water-soluble UV-curable resins, inhibitors, water, and other additives make up water-soluble UV-curable coatings, among which water-soluble UV-curable resins play an important role in the system, which determines the basic properties of the final coating, such as hardness, adhesion, flexibility, and aging resistance.

[0004] Prepolymers that contain both hydrophilic groups and unsaturated groups in their molecules belong to water-soluble photocurable resins. They can not only undergo photocuring reactions to achieve rapid crosslinking, but can also use deionized water as a dispersion medium to reduce the viscosity of the coating, which has the advantages of environmental protection and energy saving. Commonly used hydrophilic groups include carboxyl, amino, hydroxyl, amide, ether, etc.; unsaturated groups usually refer to methacryloyl or allyl. Water is not only a diluent in the system, but also a dispersion medium in the system, which can reduce the addition of reactive diluents.

[0005] Water-soluble photocurable resin has the following advantages: 1. Water is the most convenient and cheapest raw material; 2. The reduction in the amount of active diluent added also reduces irritating odors, VOCs and other odors; 3. It is suitable for a variety of coating equipment, especially safe for spraying; 4. It can avoid the shrinkage of solid volume caused by the use of active diluents; 5. It can reduce costs and achieve thin coatings; 6. The reaction equipment is easy to clean. Water-soluble UV-curable coatings are very promising coating varieties. In addition to the various advantages mentioned above, water-soluble UV-curable coatings have another very important feature, which is that they can have both high hardness and good flexibility.

[0006] Aluminum alloys have been widely valued due to their excellent comprehensive properties. Components of different types and working conditions have different requirements for the use of aluminum alloy materials, and some properties of aluminum alloys are not ideal, such as high temperature resistance, alkali resistance and

[0007] In order to improve the surface properties such as corrosion resistance, an oxide film or surface coating is usually prepared on the surface to expand the application range of aluminum alloy materials and extend their service life.

[0008] The research on it is the most in-depth, and it occupies an extremely important position because of its simple operation and excellent product performance.

[0009] Anodizing improves the wear resistance, corrosion resistance or other functionality and decorative properties of the aluminum surface, and still retains the metallic luster and metallic texture after treatment. However, the anodized film is full of micropores, and the new film layer is highly active and has extremely strong adsorption. Although this porous characteristic gives the anodized film coloring and other functional capabilities, after adsorbing pollutants, its corrosion resistance, weather resistance and pollution resistance are difficult to meet the requirements of use. Therefore, in order to make up for defects such as corrosion resistance and obtain an oxide film with good comprehensive performance, aluminum alloys must be sealed after anodizing treatment, which can effectively reduce its staining and improve its corrosion resistance and electrical insulation.

[0010] From the perspective of the contact area with the outside world, if these microporous structures are not sealed, a large area of ​​the micropores will be exposed, thereby increasing the corrosion rate. Therefore, the oxide film generated by anodizing must be sealed to reduce the effective area of ​​the oxide film in the corrosive environment, thereby improving the corrosion resistance and wear resistance of the oxide film.

[0011] At present, the main methods of sealing are cold sealing, hot sealing and normal temperature sealing. Boiling water sealing and high temperature steam sealing are both hot sealing. The principle of this sealing method is that the aluminum oxide in the oxide film reacts with pure water close to the boiling point to produce corrosion-resistant boehmite AlO(OH). Since the volume of AlO(OH) is larger than that of aluminum oxide, the original micropores can be filled, blocking the entry of external corrosive substances, thereby achieving the effect of sealing the micropores. NiF2 is most commonly used for cold sealing technology. After the nickel salt is dissolved in water, it is adsorbed on the oxide film. Hydrolysis technology is used to produce hydroxide precipitation, thereby filling the micropores on the surface. Medium temperature sealing generally uses nickel acetate for sealing. The sealing process is roughly as follows: Ni2+ is hydrolyzed to generate Ni(OH) deposited in the micropores, and at the same time, the aluminum alloy oxide film is converted into hydrated aluminum oxide with a boehmite structure, so that the micropores are filled and the purpose of sealing is achieved. It can be seen from the above sealing process that a deposition reaction will occur during the sealing process, which will completely change the chemical composition in the pores and the pore structure. Therefore, organic sealing has appeared this year, mainly by plugging the pores with organic matter or coatings, which can effectively improve the density of the film layer and the corrosion resistance while maintaining the complete pore structure. In addition, the coating does not use harmful substances such as nickel salts and fluorides, which is harmless to the human body and is also beneficial to environmental protection.

[0012] From the above content, it can be seen that aluminum alloy or other valve metals must be post-processed after anodizing, especially sealing post-processing, that is, it is necessary to choose between chemical reaction sealing and polymer coating sealing. If the anodized pore structure needs to be maintained, polymer coating sealing is the best. However, for aluminum alloy surface treatment merchants, they do not know what kind of coating the customer needs to apply on the aluminum alloy surface, which limits the production process and maintenance process of the aluminum alloy. Summary of the invention

[0013] Based on the above content, the present invention provides a UV-cured epoxy resin coating, which has extremely high permeability pore performance and can effectively maintain the anodized pore structure. After anodizing the aluminum alloy, the coating is directly used to treat the aluminum alloy. The coating coating is a transition layer. Although the physical and chemical properties are not high, it is extremely easy to peel off in a paint stripper. Customers can use conventional paint stripping methods to peel off the coating coating as needed, and then apply various coatings as needed. That is, a water-based coating composite material of the present invention is used as a transition material, which can meet various customer needs.

[0014] A method for preparing a water-based coating composite material comprises the following processing steps:

[0015] (1) Metal surface pretreatment: The metal was immersed in acetone and ultrasonically cleaned for 15 min to remove grease, then washed with tap water, taken out and dried, and then the natural oxide layer was cleaned with a 1 M sodium hydroxide solution, and repeatedly rinsed with distilled water, and then electrochemically polished in a 1:4 volume ratio of perchloric acid ethanol mixed solution for 3 min. The electrochemical polishing voltage was 17 V, the temperature was 12 °C, and the deionized water was used for cleaning.

[0016] (2) Anodizing and pore expansion to obtain a micron pore array: The electrolyte used for anodizing is composed of 2-3wt.% H3PO4, 1-1.5wt.% oxalic acid, 1-2wt.% aluminum oxalate and 10-14mL / L ethylene glycol aqueous solution. The anodizing parameters are: voltage 180-200V, time 20-40min, temperature 1-5℃.

[0017] Phosphoric acid used for hole expansion: 4-6wt.%, temperature 10-15℃, time 60-70min.

[0018] (3) Deionized water cleaning and freezing: Deionized water cleaning is rinsing with cold water at 3-5℃ for 10-15min. After rinsing, a layer of water film is formed on the surface of the aluminum alloy, and then it is frozen in a refrigerator at -10~-5℃ for 1-2h.

[0019] (4) Vacuum freeze drying, freeze drying in a freeze dryer for 5-6 hours;

[0020] (5) Prepare water-based paint and spray it on the surface of the vacuum freeze-dried metal substrate:

[0021] The composition comprises the following components in parts by weight:

[0022] 10-30 parts of waterborne epoxy acrylate resin,

[0023] 20-35 parts of waterborne polyurethane acrylate resin,

[0024] 10-15 parts of propylene glycol diacrylate,

[0025] 15-20 parts of tricarboxymethyl propane triacrylate,

[0026] Pigment 5-30 parts,

[0027] 2-6 parts of photoinitiator,

[0028] 1-5 parts of dispersant,

[0029] 1-2 parts wetting agent,

[0030] 1-2 parts of defoamer,

[0031] 10-30 parts of solvent,

[0032] The photoinitiator is at least one of photoinitiator TPO or photoinitiator 1173.

[0033] The pigment is phthalocyanine blue, iron oxide red, phthalocyanine green or carbon black.

[0034] The solvent is a mixed solvent of water and ethanol in a mass ratio of 2:1.

[0035] The defoaming agent is an organosilicon defoaming agent, the wetting agent is an organosilicon wetting agent or a surfactant, and the dispersant is at least one of BYK190, BYK193, and BYK198.

[0036] (6) Negative pressure drying (first vacuum and then heating) The process of vacuum drying is as follows: vacuum to -0.09~-0.05MPa, maintain for 1-2min, and then increase the temperature to 50℃ at 10℃ / min and keep warm for 1-2min.

[0037] (7) UV light curing: The energy used for UV light curing is 600-700mj / cm 2 , time is 10-15min.

[0038] The metal is selected from one of aluminum alloy, titanium alloy, magnesium alloy or stainless steel.

[0039] The electrolyte used in the anodization of the present invention is a mixed acid. Using two or more acids as the electrolyte for anodization can effectively combine the advantages of different acid anodizations and avoid some disadvantages, thereby obtaining an anodized film with better performance. The electrolyte used is composed of 2-3wt.% H3PO4, 1-1.5wt.% oxalic acid, 1-2wt.% aluminum oxalate and 10-14mL / L ethylene glycol aqueous solution. The anodization parameters are: voltage 180-200V, time 20-40min, temperature 1-5°C. In the process of preparing the electrolyte, since aluminum oxalate is insoluble in alcohol and water, it should be dissolved in phosphoric acid first and then diluted with water. The voltage used in the above-mentioned anodizing process is 180-200V. The voltage is relatively high and obvious ablation will occur. Adding aluminum oxalate to the electrolyte can effectively prevent breakdown and ablation. In order to further avoid the above-mentioned phenomenon, anodizing is carried out at low temperature as much as possible, within the temperature range of 1-5°C. In order to ensure the orderliness of the pore arrangement, the reaction needs to be carried out at low temperature. Under low temperature-high voltage conditions, the dissolution rate of aluminum oxide increases, and the chemical equilibrium proceeds in the direction of dissolution, so the pore size of the obtained aluminum oxide film becomes larger. In addition, the concentration of phosphoric acid and oxalic acid in the mixed acid is relatively low, which is conducive to the formation of relatively large pores. Ethylene glycol can promote the smooth progress of anodization, and the obtained array is relatively regular. After anodization, the obtained pore size is still small, and pore expansion treatment is required to increase the coating amount of water-based paint entering the pores. After pore expansion with phosphoric acid, the pore size is 0.7-0.9μm. If the pore expansion continues, the pore spacing becomes smaller, which is not conducive to the stability of the pores. Figure 1 and attached Figure 2 shown.

[0040] As mentioned above, after the pore expansion, the structural stability of the porous layer in the oxide film will decrease, but a large amount of pore expansion corrosion liquid will remain inside the pore. Only immersion cleaning cannot effectively remove the acid in the nanopores, and direct drying will directly affect the structure of the pores. Therefore, it is necessary to effectively remove the acid in the nanopores and effectively maintain the pore structure. Vacuum freeze drying is the most preferred method.

[0041] After clearing the liquid in the pores, the pores are filled and sealed with organic coatings. Generally, the coatings are self-crosslinked or cured with two-component curing agents. For self-crosslinking curing, the time cannot be determined. The coating may be partially cured before it completely enters the pores. For example, curing occurs during the drying process, blocking the pores. For two-component curing agents, there is still a problem of curing agent dispersion, which is still not conducive to controlling the timing of curing. Therefore, in order to allow the coating to completely enter the holes before curing, UV curing coatings are selected.

[0042] The UV curing coating of the present invention comprises the following components in parts by weight:

[0043] 10-30 parts of waterborne epoxy acrylate resin,

[0044] 20-35 parts of waterborne polyurethane acrylate resin,

[0045] 10-15 parts of propylene glycol diacrylate,

[0046] 15-20 parts of tricarboxymethyl propane triacrylate,

[0047] Pigment 5-30 parts,

[0048] 2-6 parts of photoinitiator,

[0049] 1-5 parts of dispersant,

[0050] 1-2 parts wetting agent,

[0051] 1-2 parts of defoamer,

[0052] 20-40 parts solvent.

[0053] The photoinitiator is at least one of photoinitiator TPO or photoinitiator 1173.

[0054] The pigment is phthalocyanine blue, iron oxide red, phthalocyanine green or carbon black.

[0055] The solvent is a mixed solvent of water and ethanol in a mass ratio of 2:1.

[0056] The defoaming agent is an organosilicon defoaming agent, the wetting agent is an organosilicon wetting agent or a surfactant, and the dispersant is at least one of BYK190, BYK193, and BYK198.

[0057] Negative pressure drying: As mentioned above, if the spraying process cannot be effectively controlled, bubbles will form on the coating surface. The presence of bubbles directly affects the amount of paint filling into the pores. In order to effectively remove bubbles and increase the amount of paint filling in the pores, negative pressure drying is required. The purpose of negative pressure is twofold. One is to remove bubbles in the paint, and the other is to remove excess solvent in the paint. Finally, UV drying is performed to obtain a composite material in which the paint can be completely filled into the pores. Figure 3 , attached Figure 4 , there is no plasmolysis or bubbles in the pores of the coating.

[0058] As an example, the present invention uses the following paint stripper, the paint stripper components are 26.8wt.% benzyl alcohol, 12.4wt.% N,N-methylpyrrolidone, 6.2wt.% diethylene glycol butyl ether, 22.7wt.% hydrogen peroxide, 1wt.% sodium dodecylbenzene sulfonate, 1wt.% OP-10, 1wt.% methyl cellulose, 21.6wt.% water, 6.2wt.% acetone, 1wt.% propionic acid, and the paint stripping conditions are to directly immerse the above-mentioned coating composite transition material in the above-mentioned exemplary paint stripper solution, and the above-mentioned solution has no sealing effect. After stripping, the aluminum alloy substrate is directly cleaned, and the pore structure of the anodized film on the surface of the aluminum alloy substrate is complete, and there is no collapse or sealing phenomenon in the pores. Then, the aluminum alloy substrate is inorganically sealed, hydrated and sealed as needed, or coated with other required coatings again.

[0059] Beneficial technical effects

[0060] (1) In the prior art, the use direction of anodized aluminum alloys is unclear. Different customers have different coating requirements for different applications. Therefore, a semi-finished aluminum alloy composite material is needed. The surface coating material of the aluminum alloy composite material provided by the present invention can effectively enter the anodized pores and can effectively maintain the pore structure after curing.

[0061] (2) The coating provided by the present invention is easy to peel off and can be easily peeled off in a conventional paint stripper. After peeling, hydrothermal sealing, inorganic salt sealing, or coating polymer sealing can be selected.

[0062] (3) The pores obtained by anodization are nano-micron pores with a pore size of 0.7-0.9 μm and a thickness of 10-20 μm. Through freeze drying, the pore structure can be effectively maintained, facilitating the subsequent penetration of the coating.

[0063] (4) The coating process uses negative pressure vacuum to promote the entry of coating and accelerate the evaporation of solvent, which is conducive to the complete entry of coating into the pores. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Attached Figure 1 Cross-sectional view of the anodized channels obtained by the preparation process in Example 2.

[0065] Attached Figure 2 Top view of the anodized channels obtained by the preparation process in Example 2.

[0066] Attached Figure 3 The coating-filled composite material obtained in Example 2.

[0067] Attached Figure 4 The coating-filled composite material obtained in Example 2. DETAILED DESCRIPTION Example

[0068] A method for preparing a water-based coating composite material comprises the following processing steps:

[0069] (1) Metal surface pretreatment: Immerse the aluminum alloy in acetone and ultrasonically clean it for 15 minutes to remove grease, then rinse it with tap water, take it out and dry it, then clean the natural oxide layer with a 1M sodium hydroxide solution, and rinse it repeatedly with distilled water, then electrochemically polish it in a 1:4 volume ratio of perchloric acid ethanol mixed solution for 3 minutes, the electrochemical polishing voltage is 17V, the temperature is 12℃, and it is rinsed with deionized water.

[0070] (2) Anodization and pore expansion to obtain a micron pore array: The electrolyte used for anodization was composed of 2wt.% H3PO4, 1wt.% oxalic acid, 1wt.% aluminum oxalate and 10mL / L ethylene glycol aqueous solution. The anodization parameters were: voltage 180V, time 20min, temperature 1°C, phosphoric acid used for pore expansion: 4wt.%, temperature 10°C, time 60min.

[0071] (3) Deionized water washing and freezing: In step (3), the deionized water washing is performed by rinsing with 3°C cold water for 10 min, followed by freezing in a -10°C refrigerator for 1 h, and then placing in a freeze dryer for drying for 5 h.

[0072] (4) Vacuum freeze drying.

[0073] (5) preparing a water-based coating and spraying it on the surface of the vacuum freeze-dried metal substrate, wherein the water-based coating comprises the following components in parts by weight:

[0074] 10 parts of waterborne epoxy acrylate resin,

[0075] 20 parts of waterborne polyurethane acrylate resin,

[0076] 10 parts of propylene glycol diacrylate,

[0077] 15 parts of tricarboxymethyl propane triacrylate,

[0078] 5 parts of pigment,

[0079] 2 parts of photoinitiator,

[0080] 1 part of dispersant,

[0081] 1 part wetting agent,

[0082] 1 part defoamer,

[0083] 20 parts of solvent,

[0084] The photoinitiator is photoinitiator TPO.

[0085] The pigment is phthalocyanine blue.

[0086] The solvent is a mixed solvent of water and ethanol in a mass ratio of 2:1.

[0087] The defoaming agent is an organosilicon defoaming agent, the wetting agent is an organosilicon wetting agent, and the dispersant is BYK190.

[0088] (6) Negative pressure drying: The negative pressure drying process is as follows: pump the negative pressure to -0.09MPa, maintain for 1 minute, and then increase the temperature to 50℃ at 10℃ / min and keep warm for 1 minute.

[0089] (7) UV light curing: The energy used for UV light curing is 600mj / cm 2 , time is 10 minutes.

[0090] Example 2

[0091] A method for preparing a water-based coating composite material comprises the following processing steps:

[0092] (1) Metal surface pretreatment: Immerse the aluminum alloy in acetone and ultrasonically clean it for 15 minutes to remove grease, then rinse it with tap water, take it out and dry it, then clean the natural oxide layer with a 1M sodium hydroxide solution, and rinse it repeatedly with distilled water, then electrochemically polish it in a 1:4 volume ratio of perchloric acid ethanol mixed solution for 3 minutes, the electrochemical polishing voltage is 17V, the temperature is 12℃, and it is rinsed with deionized water.

[0093] (2) Anodization and pore expansion to obtain a micron pore array: The electrolyte used for anodization was composed of 2.5wt.% H3PO4, 1.25wt.% oxalic acid, 1.5wt.% aluminum oxalate and 12mL / L ethylene glycol aqueous solution. The anodization parameters were: voltage 190V, time 30min, temperature 3°C, phosphoric acid used for pore expansion: 5wt.%, temperature 12.5°C, time 65min.

[0094] (3) Deionized water washing and freezing: In step (3), the deionized water washing is performed by rinsing with 4°C cold water for 12.5 min, followed by freezing in a -7.5°C refrigerator for 1.5 h, and then placing in a freeze dryer for drying for 5.5 h.

[0095] (4) Vacuum freeze drying.

[0096] (5) preparing a water-based coating and spraying it on the surface of the vacuum freeze-dried metal substrate, wherein the water-based coating comprises the following components in parts by weight:

[0097] 20 parts of waterborne epoxy acrylate resin,

[0098] 27.5 parts of waterborne polyurethane acrylate resin,

[0099] 12.5 parts of propylene glycol diacrylate,

[0100] 17.5 parts of tricarboxymethyl propane triacrylate,

[0101] Pigment 17.5 parts,

[0102] 4 parts of photoinitiator,

[0103] 3 parts of dispersant,

[0104] 1.5 parts of wetting agent,

[0105] 1.5 parts of defoamer,

[0106] 30 parts of solvent,

[0107] The photoinitiator is photoinitiator 1173.

[0108] The pigment is phthalocyanine green.

[0109] The solvent is a mixed solvent of water and ethanol in a mass ratio of 2:1.

[0110] The defoaming agent is an organosilicon defoaming agent, the wetting agent is an organosilicon wetting agent, and the dispersant is BYK193.

[0111] (6) Negative pressure drying: The negative pressure drying process is as follows: pump the negative pressure to -0.097MPa, maintain for 1.5min, and then increase the temperature to 50℃ at 10℃ / min and keep warm for 1.5min.

[0112] (7) UV light curing: The energy used for UV light curing is 650mj / cm 2 , time is 12.5min.

[0113] Example 3

[0114] A method for preparing a water-based coating composite material comprises the following processing steps:

[0115] (1) Metal surface pretreatment: Immerse the aluminum alloy in acetone and ultrasonically clean it for 15 minutes to remove grease, then rinse it with tap water, take it out and dry it, then clean the natural oxide layer with a 1M sodium hydroxide solution, and rinse it repeatedly with distilled water, then electrochemically polish it in a 1:4 volume ratio of perchloric acid ethanol mixed solution for 3 minutes, the electrochemical polishing voltage is 17V, the temperature is 12℃, and it is rinsed with deionized water.

[0116] (2) Anodization and pore expansion to obtain a micron pore array: The electrolyte used for anodization was composed of 3wt.% H3PO4, 1.5wt.% oxalic acid, 2wt.% aluminum oxalate and 14mL / L ethylene glycol aqueous solution. The anodization parameters were: voltage 200V, time 40min, temperature 5°C, phosphoric acid used for pore expansion: 6wt.%, temperature 15°C, time 70min.

[0117] (3) Deionized water washing and freezing: In step (3), the deionized water washing is performed by rinsing with 5°C cold water for 15 minutes, followed by freezing in a -5°C refrigerator for 2 hours, and then placing in a freeze dryer for drying for 6 hours.

[0118] (4) Vacuum freeze drying.

[0119] (5) preparing a water-based coating and spraying it on the surface of the vacuum freeze-dried metal substrate, wherein the water-based coating comprises the following components in parts by weight:

[0120] 30 parts of waterborne epoxy acrylate resin,

[0121] 35 parts of waterborne polyurethane acrylate resin,

[0122] 15 parts of propylene glycol diacrylate,

[0123] 20 parts of tricarboxymethyl propane triacrylate,

[0124] 30 parts of pigment,

[0125] 6 parts of photoinitiator,

[0126] Dispersant 5 parts,

[0127] 2 parts of wetting agent,

[0128] 2 parts of defoamer,

[0129] 40 parts of solvent,

[0130] The photoinitiator is at least one of the photoinitiators 1173 .

[0131] The pigment is red iron oxide.

[0132] The solvent is a mixed solvent of water and ethanol in a mass ratio of 2:1.

[0133] The defoaming agent is an organosilicon defoaming agent, the wetting agent is an organosilicon wetting agent or a surfactant, and the dispersant is at least one of BYK198.

[0134] (6) Negative pressure drying: The negative pressure drying process is as follows: pump the negative pressure to -0.05MPa, maintain for 1-2 minutes, and then increase the temperature to 50℃ at 10℃ / min and keep warm for 2 minutes.

[0135] (7) UV light curing: The energy used for UV light curing is 700mj / cm 2 , time is 15 minutes.

[0136] Comparative Example 1

[0137] The UV ink is Lancolu L-6135 UV epoxy resin ink, the coating method is spraying, and the energy used for UV light curing is 650mj / cm 2 The preparation process of the composite material is substantially the same as that of Example 2.

[0138] Comparative Example 2

[0139] The coating is ordinary water-based epoxy resin, and the preparation process of the composite material is substantially the same as that of Example 2.

[0140] The adhesion test is carried out by coating pull-off method adhesion determination according to GB / T 5210-2006.

[0141] Adhesion tests were performed on Examples 1-3 and Comparative Examples 1-2, wherein the binding force obtained in Example 1 was 5.23±0.27; the binding force obtained in Example 2 was 6.03±0.19; the binding force obtained in Example 3 was 5.81±0.23; the binding force obtained in Comparative Example 1 was 3.92±0.69; and the binding force obtained in Comparative Example 2 was 2.34±0.79.

[0142] From the above results, it can be seen that the bonding strength obtained in Example 2 of the present invention is the highest, and the fluctuation range of the bonding force is small, that is, the bonding strength between the overall coating and the substrate is relatively uniform. It can be seen that the UV coating of the present invention can be filled into the channel more evenly, and the curing process is more uniform.

[0143] In order to prove the protective effect of the coating of the present invention on the anodic oxide film, that is, after the coating is peeled off, it will not affect the oxide film, the comparative example 3 is further characterized.

[0144] Comparative Example 3

[0145] The composite material prepared in Example 3 was immersed in a paint stripping solution consisting of 26.8 wt.% benzyl alcohol, 12.4 wt.% N,N-methylpyrrolidone, 6.2 wt.% diethylene glycol butyl ether, 22.7 wt.% hydrogen peroxide, 1 wt.% sodium dodecylbenzene sulfonate, 1 wt.% OP-10, 1 wt.% methyl cellulose, 21.6 wt.% water, 6.2 wt.% acetone, and 1 wt.% propionic acid for 5 minutes. After complete stripping, the aluminum substrate was removed, and then washed with deionized water, rinsed with 4°C cold water, and the rinsing time was 12.5 minutes, and then frozen in a -7.5°C refrigerator for 1.5 hours, and then placed in a freeze dryer and dried for 5.5 hours.

[0146] Vacuum freeze drying.

[0147] A water-based coating is prepared and sprayed on the surface of the vacuum freeze-dried metal substrate. The water-based coating includes the following components in parts by weight:

[0148] 20 parts of waterborne epoxy acrylate resin,

[0149] 27.5 parts of waterborne polyurethane acrylate resin,

[0150] 12.5 parts of propylene glycol diacrylate,

[0151] 17.5 parts of tricarboxymethyl propane triacrylate,

[0152] Pigment 17.5 parts,

[0153] 4 parts of photoinitiator,

[0154] 3 parts of dispersant,

[0155] 1.5 parts of wetting agent,

[0156] 1.5 parts of defoamer,

[0157] 30 parts of solvent,

[0158] The photoinitiator is photoinitiator 1173.

[0159] The pigment is phthalocyanine green.

[0160] The solvent is a mixed solvent of water and ethanol in a mass ratio of 2:1.

[0161] The defoaming agent is an organosilicon defoaming agent, the wetting agent is an organosilicon wetting agent, and the dispersant is BYK193.

[0162] Negative pressure drying: The negative pressure drying process is as follows: pump the negative pressure to -0.097MPa, maintain for 1.5min, then increase the temperature to 50℃ at 10℃ / min and keep warm for 1.5min.

[0163] UV light curing: The energy used for UV light curing is 650mj / cm 2 , time is 12.5min.

[0164] The binding strength of the product obtained in Comparative Example 3 was tested, and the binding strength of Comparative Example 3 was 5.94±0.21 MPa, which was slightly decreased and fluctuated within a small range. This proves that the UV coating obtained in the present invention can be fully and completely filled in the anodized pores, will not cause any effect on the pore array of the oxide film, and the effect of secondary utilization of the oxide film is excellent.

[0165] Comparative Example 4

[0166] A method for preparing a water-based coating composite material comprises the following processing steps:

[0167] (1) Metal surface pretreatment: Immerse the aluminum alloy in acetone and ultrasonically clean it for 15 minutes to remove grease, then rinse it with tap water, take it out and dry it, then clean the natural oxide layer with a 1M sodium hydroxide solution, and rinse it repeatedly with distilled water, then electrochemically polish it in a 1:4 volume ratio of perchloric acid ethanol mixed solution for 3 minutes, the electrochemical polishing voltage is 17V, the temperature is 12℃, and it is rinsed with deionized water.

[0168] (2) Anodization and pore expansion to obtain a micron pore array: The electrolyte used for anodization was composed of 2.5wt.% H3PO4, 1.25wt.% oxalic acid, 1.5wt.% aluminum oxalate and 12ml / L ethylene glycol aqueous solution. The anodization parameters were: voltage 190V, time 30min, temperature 3°C, phosphoric acid used for pore expansion: 5wt.%, temperature 12.5°C, time 65min.

[0169] (3) Deionized water washing and freezing: In step (3), the deionized water washing is performed by rinsing with 4°C cold water for 12.5 min, followed by freezing in a -7.5°C refrigerator for 1.5 h, and then placing in a freeze dryer for drying for 5.5 h.

[0170] (4) Vacuum freeze drying.

[0171] (5) preparing a water-based coating and spraying it on the surface of the vacuum freeze-dried metal substrate, wherein the water-based coating comprises the following components in parts by weight:

[0172] 20 parts of waterborne epoxy acrylate resin,

[0173] 27.5 parts of waterborne polyurethane acrylate resin,

[0174] 12.5 parts of propylene glycol diacrylate,

[0175] 17.5 parts of tricarboxymethyl propane triacrylate,

[0176] Pigment 17.5 parts,

[0177] 4 parts of photoinitiator,

[0178] 3 parts of dispersant,

[0179] 1.5 parts of wetting agent,

[0180] 1.5 parts of defoamer,

[0181] 30 parts of solvent,

[0182] The photoinitiator is photoinitiator 1173.

[0183] The pigment is phthalocyanine green.

[0184] The solvent is a mixed solvent of water and ethanol in a mass ratio of 2:1.

[0185] The defoaming agent is an organosilicon defoaming agent, the wetting agent is an organosilicon wetting agent, and the dispersant is BYK193.

[0186] (6) UV light curing: The energy used for UV light curing is 650mj / cm 2 , time is 12.5min.

[0187] Comparative Example 4 is mainly based on Example 2, but reduces the step of vacuum drying the coating, reduces solvent evaporation and the amount of filling entering the pores, decreases the bonding force, increases the fluctuation, and the result is 5.45±0.57.

[0188] Comparative Example 5

[0189] The composite material prepared in Comparative Example 3 was immersed in a paint stripping solution consisting of 26.8 wt.% benzyl alcohol, 12.4 wt.% N,N-methylpyrrolidone, 6.2 wt.% diethylene glycol butyl ether, 22.7 wt.% hydrogen peroxide, 1 wt.% sodium dodecylbenzene sulfonate, 1 wt.% OP-10, 1 wt.% methyl cellulose, 21.6 wt.% water, 6.2 wt.% acetone, and 1 wt.% propionic acid for 5 minutes. After complete stripping, the aluminum substrate was removed, and then the composite material was washed with deionized water at 4°C for 12.5 minutes, and then frozen in a -7.5°C refrigerator for 1.5 hours, and then placed in a freeze dryer for 5.5 hours.

[0190] Vacuum freeze drying.

[0191] A water-based coating is prepared and sprayed on the surface of the vacuum freeze-dried metal substrate. The water-based coating includes the following components in parts by weight:

[0192] 20 parts of waterborne epoxy acrylate resin,

[0193] 27.5 parts of waterborne polyurethane acrylate resin,

[0194] 12.5 parts of propylene glycol diacrylate,

[0195] 17.5 parts of tricarboxymethyl propane triacrylate,

[0196] Pigment 17.5 parts,

[0197] 4 parts of photoinitiator,

[0198] 3 parts of dispersant,

[0199] 1.5 parts of wetting agent,

[0200] 1.5 parts of defoamer,

[0201] 30 parts of solvent,

[0202] The photoinitiator is photoinitiator 1173.

[0203] The pigment is phthalocyanine green.

[0204] The solvent is a mixed solvent of water and ethanol in a mass ratio of 2:1.

[0205] The defoaming agent is an organosilicon defoaming agent, the wetting agent is an organosilicon wetting agent, and the dispersant is BYK193.

[0206] Negative pressure drying: The negative pressure drying process is as follows: pump the negative pressure to -0.097MPa, maintain for 1.5min, then increase the temperature to 50℃ at 10℃ / min and keep warm for 1.5min.

[0207] UV light curing: The energy used for UV light curing is 650mj / cm 2 , time is 12.5min.

[0208] The binding strength of the product obtained in Comparative Example 4 was tested, and the binding strength of Comparative Example 4 was 4.79±0.32 MPa, and the binding strength and the binding strength fluctuated within a small range. This proves that if the negative pressure drying is deleted, the amount of paint filling in the pores will be reduced, thereby causing the collapse or rupture of the pores inside the oxide film, resulting in a reduction in the secondary utilization effect of the anodized film aluminum oxide.

[0209] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A method for preparing a semi-finished water-based coating composite material, characterized in that The processing steps include: (1) Metal surface pretreatment; (2) Anodizing and pore expansion to obtain micron-channel arrays; (3) Deionized water washing and freezing; (4) Vacuum freeze drying; (5) Preparing a water-based coating and spraying it on the surface of the vacuum freeze-dried metal substrate, wherein the metal is selected from one of aluminum alloy, titanium alloy, magnesium alloy or stainless steel, and the water-based coating comprises the following components in parts by weight: 10-30 parts of waterborne epoxy acrylate resin, 20-35 parts of waterborne polyurethane acrylate resin, 10-15 parts of propylene glycol diacrylate, 15-20 parts of tricarboxymethyl propane triacrylate, Pigment 5-30 parts, 2-6 parts of photoinitiator, Dispersant 1-5 parts, 1-2 parts of wetting agent, 1-2 parts of defoaming agent, 20-40 parts of solvent, (6) Negative pressure drying; (7) UV light curing; The photoinitiator is at least one of photoinitiator TPO or photoinitiator 1173; The pigment is phthalocyanine blue, iron oxide red, phthalocyanine green or carbon black; The solvent is a mixed solvent of water and ethanol in a mass ratio of 2:1; The defoaming agent is an organosilicon defoaming agent, the wetting agent is an organosilicon wetting agent, and the dispersant is at least one of BYK190, BYK193, and BYK198; The electrolyte used for anodizing is composed of 2-3wt.% H3PO4, 1-1.5wt.% oxalic acid, 1-2wt.% aluminum oxalate and 10-14mL / L ethylene glycol aqueous solution. The anodizing parameters are: voltage 180-200V, time 20-40min, temperature 1-5°C; the phosphoric acid used for pore expansion is 4-6wt.%, temperature 10-15°C, and time 60-70min.

2. The method for preparing a semi-finished water-based coating composite material according to claim 1, characterized in that The pretreatment process is as follows: immerse the metal in acetone and ultrasonically clean it for 15 minutes to remove grease, then wash it with tap water, take it out and dry it, then clean the natural oxide layer with a 1M sodium hydroxide solution, and rinse it repeatedly with distilled water, and then electrochemically polish it in a 1:4 volume ratio of perchloric acid ethanol mixed solution for 3 minutes, the electrochemical polishing voltage is 17V, the temperature is 12°C, and it is washed with deionized water.

3. The method for preparing a semi-finished water-based coating composite material according to claim 1, characterized in that The step (3) of deionized water washing is performed by rinsing with cold water at 3-5°C for 10-15 minutes, and then freezing in a -10~-5°C refrigerator for 1-2 hours, and then placing in a freeze dryer for drying for 5-6 hours.

4. The method for preparing a semi-finished water-based coating composite material according to claim 1, characterized in that The negative pressure drying process is as follows: pump the negative pressure to -0.09~-0.05MPa, maintain for 1-2min, and then increase the temperature to 50℃ at 10℃ / min and keep warm for 1-2min.

5. The method for preparing a semi-finished water-based coating composite material according to claim 1, characterized in that The energy used for UV curing is 600-700mj / cm 2 , time is 10-15min.

Citation Information

Patent Citations

  • Hole-sealing method for anode oxide film of light metal material

    CN101597784A

  • Waterborne UV type stainless steel protecting coating with excellent CNC resistance

    CN108410346A

  • Preparation method of high-stability metal material coated with resin on surface

    CN108995128A

  • Application of water-based coating composition

    CN115304964A

  • Water-based coating composition

    CN115403993A